Characteristics of acute febrile illness and determinants of illness recovery among adults presenting to Singapore primary care clinics. Issue 1 (December 2016) - Tun, Zaw; Moorthy, Mahesh; Linster, Martin; Su, Yvonne; Coker, Richard; Ooi, Eng; Low, Jenny; Smith, Gavin; Tam, Clarence
Abstract Background Undifferentiated acute febrile illness (AFI) is a common presentation among adults in primary care settings in Singapore but large gaps exist in the understanding of the characteristics of these patients. We studied clinical and epidemiological characteristics of AFI patients and factors associated with delayed recovery from AFI. Methods We performed a secondary data analysis using data from the Early DENgue infection and outcome (EDEN) study on 2046 adult patients presenting at 5 Singapore polyclinics between December 2007 and February 2013 with a history of fever (≥38 °C) for less than 72 h. We used an accelerated failure time model to investigate factors associated with delayed recovery from AFI. Results The mean age of patients was 36.6 years, 65 % were male, 51 % were of Chinese ethnicity, and 75 % lived in public housing. Median illness duration was 5 days (interquartile range, 3–7). In multivariable analysis, the unemployed and white collar workers had longer illness duration compared with blue collar workers (time ratio (TR), 1.10; 95 % confidence interval (CI), 1.03–1.17 and TR, 1.08; 95 % CI, 1.02–1.15, respectively). Patients with more symptoms at initial consultation had slower recovery (TR, 1.03 per additional symptom; 95 % CI, 1.02–1.03). Other clinical factors were also associated with longer duration of illness, including use of analgesics (TR, 1.21; 95 % CI, 1.15–1.28); use of cough medicines (TR, 1.14; 95 % CI, 1.08–1.20); use of antibiotics (TR, 1.14; 95 % CI, 1.07–1.21); and hospitalization (TR, 1.59; 95 % CI, 1.39–1.82). Compared to patients with normal WBC count at first consultation, those with low WBC count had slower recovery (TR, 1.14; 95 % CI, 1.07–1.21), while the reverse was observed among patients with high WBC count (TR, 0.94; 95 % CI, 0.88–1.00). Conclusions Differences in illness duration among different types of employment may reflect differences in their underlying general health status. Early identification of factors delaying recovery could help triage management in a primary care setting. In-depth characterization of fever etiology in Singapore will improve surveillance and control activities.